Pamdesku: An ABCD-Driven Digital Solution for PAMDes Service Management - Priandani, Nurizal Dwi; Aziz, Okta Qomaruddin; Hariri, Fajar Rohman; Hariyanto, Wahyu; Utama, Shoffin Nahwa (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
Village-owned drinking water enterprises in Indonesia have required better tools for metering, billing, and payment to replace fragmented paper-based workflows. This work aimed to design, implement, and evaluate a web-based information system (PAMDESKU) for a village water enterprise, while strengthening local capacity through the Asset-Based Community Development (ABCD) approach. A web-based application was developed and deployed with modules for customer data, tariffs, meter readings, billing, payments, and reporting, alongside safeguards for authorization, logging, and backup, which was named PAMDESKU. Baseline usability had been poor; after implementation and mentoring, the SUS score increased to the “Good to Use” range, with concurrent reductions in data entry errors and reporting time and improved transparency of billing information. The coupling of ABCD with end-to-end digitalization enabled a locally owned and sustainable service transformation. The approach yielded measurable usability and efficiency improvements and offers a replicable pathway for other village enterprises pursuing Smart Village objectives.